2002
DOI: 10.1002/bit.10457
|View full text |Cite
|
Sign up to set email alerts
|

Limiting factors in Escherichia coli fed‐batch production of recombinant proteins

Abstract: Fed-batch production of recombinant beta-galactosidase in E. coli was studied with respect to the specific growth rate at induction. The cultivations were designed to induce protein production by IPTG at a glucose feed rate corresponding to high mu = 0.5 h(-1)) or low (mu = 0.1 h(-1)) specific growth rate. Protein production rate was approximately 100% higher at the higher specific growth rate, resulting in the accumulation of beta-galactosidase up to 30% of the total cell protein. Transcription analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 27 publications
6
120
1
Order By: Relevance
“…However, increased copy number might reasonably be expected to exert a knock-on effect on transcription and translation, both of which may become rate-limiting due to a lack of resources, such as precursors and energy [47], as has been previously reported for recombinant protein production in E. coli [62,93]. However, in Pichia it has been proposed that it is more likely that any limitations are due to post-translational events, such as folding within the endoplasmic reticulum (ER), membrane translocation and signal sequence processing [47].…”
Section: Gene Dosagementioning
confidence: 94%
“…However, increased copy number might reasonably be expected to exert a knock-on effect on transcription and translation, both of which may become rate-limiting due to a lack of resources, such as precursors and energy [47], as has been previously reported for recombinant protein production in E. coli [62,93]. However, in Pichia it has been proposed that it is more likely that any limitations are due to post-translational events, such as folding within the endoplasmic reticulum (ER), membrane translocation and signal sequence processing [47].…”
Section: Gene Dosagementioning
confidence: 94%
“…Fed-batch fermentations were used to assess E. coli MDS40 at three different the fed-batch growth rates: 0.15 h −1 (low), 0.25 h −1 (intermediate), and 0.5 hr −1 (high), where the batch phase growth rates were not different. The parent strain, E. coli MG1655, was only assessed at 0.25 h −1 , as the behavior of E. coli MG1655 and other related strains has been well investigated with respect to recombinant protein productivity at these controlled growth rates (Curless et al, 1990;Hellmuth et al, 1994;Sanden et al, 2003;Turner et al, 1994). The growth curves for E. coli MG1655 and MDS40 are shown in Figure 2.…”
Section: Fed-batch Fermentationmentioning
confidence: 99%
“…Some expression systems have extremely powerful promoters which have been observed to stress the cells or cause a metabolic burden (Glick, 1995;Haddadin and Harcum, 2005;Hoffman et al, 2002;Sanden et al, 2003;Wood and Peretti, 1990). To assess the effect of strong promoters on E. coli MDS40, the effect of changing the induction strength was investigated.…”
Section: Fed-batch Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that synthesis rates (35,38) and steady-state levels (17) of ribosomal proteins, as well as rRNA levels (36), decrease during recombinant protein synthesis in fed-batch fermentations. In the present study, the ribosomal protein decrease seemed to occur in both control and production runs.…”
Section: Vol 71 2005 Proteomic Profiling Of E Coli Fermentations 1725mentioning
confidence: 99%